Progress in pulmonary rehabilitation of Traditional Chinese Medicine and Western medicine in stable stage of chronic obstructive pulmonary disease (慢性阻塞性肺疾病稳定期的中西医肺康复研究进展) - DU Meichang (杜美昌) (中西医结合护理)
Pulmonary rehabilitation is well-established as an effective nonpharmacologic intervention for people with chronic obstructive pulmonary disease(COPD), aiming to improve the health status and quality of life. This paper reviewed studies on pulmonary rehabilitation of Traditional Chinese Medicine and Western medicine in stable stage of COPD, and explore a comprehensive rehabilitation program of integrated traditional Chinese and western medicine for patients with COPD in stable stage. (肺康复(PR)是治疗慢性呼吸系统疾病的关键, 在改善慢性阻塞性肺疾病(COPD)患者的健康状态和提高生存质量上发挥着重要作用。本研究就中西医康复疗法在COPD稳定期患者中的应用现状进行综述, 旨在为探索出一套完善的COPD稳定期中西医结合康复方案提供参考。)